Plant Species In The Honggoderpo Cemetery, Wonosobo Regency, Central Java - Irsyam, Arifin Surya Dwipa; Ristiawan, Hani; Hariri, Muhammad Rifqi; Peniwidiyanti, Peniwidiyanti; Irwanto, Rina Ratnasih (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2022)
Honggoderpo Cemetery is one of the urban green open spaces (RTH) which is located adjacent to the center of Wonosobo Regency, Central Java. This cemetery is a sacred area, so disturbances to the environment are rare, including plants. Therefore, plant diversity is still maintained...